Sosialisasi Integrasi Teknologi dalam Pembelajaran Sains Menggunakan Physics Education Technology (PhET) - Pranata, Ogi Danika; Seprianto, Seprianto; Adelia, Ismi; Darwata, Siti Riva (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
The community engagement activity was conducted using the community-based research method. The engagement began with the formation of a community and continued with socialization activities and the application of technology integration in science education. Finally, an evaluation was conducted in the form of concept comprehension tests and student perception surveys. The activities were implemented according to plan and achieved the desired goals. Firstly, students' conceptual understanding surpassed the minimum criteria (70.36). However, difficulties were still encountered by students related to concept comprehension. These difficulties need to be further investigated. Secondly, students' perception of the activities was considered excellent (84.00). They acknowledged that integrating technology using PhET could create engaging learning experiences, enhance motivation to learn, assist in understanding concepts, and encourage them to actively engage in learning. However, they still doubted whether PhET could be as beneficial as they perceived it to be in other science topics. Thus, learning activities with PhET integration are deemed suitable and evaluated for their usefulness in other science topics.